Contributions of auriculotherapy in smoking cessation: a pilot study - Roberta de Paiva Silva; Erika de Cássia Lopes Chaves; Sandra Cristina Pillon; Andréia Maria Silva; Denis da Silva Moreira; Denise Hollanda Iunes (SciELO, 2014)
Objective To evaluate the contribution of auriculotherapy in smoking cessation. Method Double-blind randomized controlled trial, conducted with 30 smokers allocated into two groups: Experimental Group (21 participants received 10 sessions of auriculotherapy at specific points for smoking) and Control Group (nine participants received auriculotherapy in points that have no effect on the focus of research). Results Auriculotherapy contributed in reducing the number of cigarettes smoked in 61.9% of participants (p=0.002), in reducing the difficult to abstain from smoking in places where it is forbidden by 38% (p=0.050) and in not smoking when ill 23.8% (p=0.025). Conclusion Given the efficacy only in terms of reducing the number of cigarettes smoked and other parameters, we suggest that future studies consider the use of auriculotherapy combined with other treatment methods, in order to achieve better results in cessation/abstinence.